If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p(x + 1)(x + -3) = 0 Reorder the terms: p(1 + x)(x + -3) = 0 Reorder the terms: p(1 + x)(-3 + x) = 0 Multiply (1 + x) * (-3 + x) p(1(-3 + x) + x(-3 + x)) = 0 p((-3 * 1 + x * 1) + x(-3 + x)) = 0 p((-3 + 1x) + x(-3 + x)) = 0 p(-3 + 1x + (-3 * x + x * x)) = 0 p(-3 + 1x + (-3x + x2)) = 0 Combine like terms: 1x + -3x = -2x p(-3 + -2x + x2) = 0 (-3 * p + -2x * p + x2 * p) = 0 (-3p + -2px + px2) = 0 Solving -3p + -2px + px2 = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'p'. p(-3 + -2x + x2) = 0 Factor a trinomial. p((-1 + -1x)(3 + -1x)) = 0Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Add 'x' to each side of the equation. -1x + x = 1 + x Combine like terms: -1x + x = 0 0 = 1 + x Simplifying 0 = 1 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 3
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Add 'x' to each side of the equation. -1x + x = -3 + x Combine like terms: -1x + x = 0 0 = -3 + x Simplifying 0 = -3 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
p = {0}
| j^2+5j=-4 | | x^2+13x=-22 | | -31=8+-6p+-7p | | 25-x/7=2 | | TC=1000+8Q | | 72=1/2(4t^2) | | 4x^2+4y^2-8x=0 | | 1*1*1*1=5 | | 16a+40= | | 25y*2n=n+y | | 85=x+-8 | | 6x/(x-1)=3 | | 54-8x=20 | | 5x-9=3(5x+3) | | 6x/(x-1)3 | | 4a+5-7a= | | -11/2/4 | | 9x^2-(7x-2)(x+3)=-12x+1 | | 8x^3+45= | | X=120+5x | | -4x-11y-9x+15y= | | x^4-2x^2+6x=0 | | 8x^3+45=2x(2x+21) | | y=2(x+3)(x+3)-32 | | y=8ln(3x-2)-4 | | y=2(x+3)-32 | | Y=2x^2-11x+18 | | Y=3.75(5) | | 10x=(50*2) | | 6h-10=6h+10 | | 11=f-4 | | 7.4r+9+2r=18 |